2016
DOI: 10.13066/kspm.2016.11.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Action observation training enhances upper extremity function in subacute stroke survivor with moderate impairment: a double-blind, randomized controlled pilot trial

Abstract: | Abstract |1 )PURPOSE: This study's aim was to investigate the effects of an action observational training in subactue stroke patients with moderate impairment. CONCLUSION: These findings suggest that action observational training may be more helpful to improve upper-extremity function than physical training only in subactue patients with moderate impairment after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…Then, 70 articles were excluded, of which, 48 articles were not RCTs, two articles applied AOT in both groups, one study applied only a single-session AOT, three studies without sufficient data for meta-analysis, five studies reported overlapped patients’ dataset and eleven studies did not use any clinical upper limb motor outcome measurement. Ultimately, seven studies were included in the present review [8, 14, 2630].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, 70 articles were excluded, of which, 48 articles were not RCTs, two articles applied AOT in both groups, one study applied only a single-session AOT, three studies without sufficient data for meta-analysis, five studies reported overlapped patients’ dataset and eleven studies did not use any clinical upper limb motor outcome measurement. Ultimately, seven studies were included in the present review [8, 14, 2630].…”
Section: Resultsmentioning
confidence: 99%
“…Totally, 276 participants with stroke were involved in this review, with 141 participants in the experimental group and 135 participants in the control group. There were two articles with 112 patients who suffered stroke less than 1 month [8, 14], two studies with 75 patients who suffered stroke between 1 and 6 months [27, 30] and one study with 16 patients who suffered stroke over 6 months [26]. One study recruited 61 subjects who suffered stroke within 6 months [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the increased cortex excitability of the premotor area and inferior parietal lobe shows that visual feedback training with "action-observation" is involved in motor learning (Zentgraf et al, 2005). Action observation training is effective in upper extremity function in stroke patients with moderate disability (Kim and Bang, 2016).…”
Section: ⅰ Introductionmentioning
confidence: 99%